Factors of Crime Boosting the Crime Ratio in Sahiwal (Pakistan) - Zubair Hussain (Web of Journals Publishing, 2023)
This study looks into the factors that are increasing the crime rate in Pakistan's division Sahiwal. Pakistan is a developing country with a population of over 220 million people and ranks 26th out of 156 countries in terms of crime rate. Pakistan has a crime index of 56.63% and a safety index of 43.37%. The study's main goal is to investigate the economic and psychological factors that are increasing crime in the Sahiwal area, as well as the role of the police and society in combating these crimes..Purposive sampling technique will be applied to conduct the case studies of 60 criminals. Data will be collected with a structural questionnaire and interview and will be analyzed by using SPSS software and Smart PLS. Descriptive and Inferential statistics (chi-square & gamma) statistics will be applied for data analysis. Expected results factor those impacting crime rates and its impact on the individual and public livings. It can also improve the crime free society.
Keywords: Crime, Investigation, Economic, Psychological, Illiteracy Rate, Unemployment, Poverty, Peace, Pakistan.